Konformitas Teman Sebaya, Konsep Diri dan Kenakalan Remaja - Suparno, * (Persona:Jurnal Psikologi Indonesia, 2013)
Abstract. Delinquency picture resembles a misbehaving adults. The proportion of variation of delinquency explained through peer conformity and self-concept. Measurement of delinquency, peer conformity and self-concept involving 100 adolescents aged 15 to 17 years. The findings showed: 1) peer conformity and self-concept significantly predicted increased delinquency, 2) correlation of peer conformity (with controlling of self-concept) with delinquency is positive and significant; 3) correlation of self-concept (with controlling of peer conformity) with delinquency is negative and significant. The research findings are discussed in the context of adolescent developmental tasks.Keywords: Self-concept, peer conformity, delinquency